Effect of Different Types of Rest-Break Interventions on Neck and Shoulder Muscle Activity, Perceived Discomfort and Productivity in Symptomatic VDU Operators: A Randomized Controlled Trial. - Nakphet, Nuttika; Chaikumarn, Montakarn; Janwantanakul, Prawit (International Journal of Occupational Safety & Ergonomics, 2014)
Objective. This study evaluated the effect of different types of activities during rest-break interventions on neck and shoulder muscle activity, muscle discomfort and productivity among symptomatic video display unit (VDU) operators performing prolonged computer terminal work. Study design and setting. Randomized controlled trial was used. Thirty symptomatic VDU operators were randomly assigned to 2 active break groups (stretching and dynamic movement) and a reference group. The subjects performed the same typing task for 60 min and received 3-min breaks after each 20 min of work. Root mean square and median frequency were calculated for neck and shoulder muscle activity. Muscle discomfort was measured with Borg's CR-10 scale. Productivity was measured by counting words. Results. There were no significant differences between the types of activities during breaks on neck and shoulder muscle activity, muscle discomfort or productivity. However, there was a significant difference in the level of muscle discomfort over time. Conclusions. Three types of activity during breaks showed a favourable effect on neck and shoulder muscle activity and productivity, and a positive effect on muscle discomfort in symptomatic VDU operators.